2023
DOI: 10.3390/antiox12051014
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Glutathione System in an Animal Model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progredient neurodegenerative disease characterized by a degeneration of the first and second motor neurons. Elevated levels of reactive oxygen species (ROS) and decreased levels of glutathione, which are important defense mechanisms against ROS, have been reported in the central nervous system (CNS) of ALS patients and animal models. The aim of this study was to determine the cause of decreased glutathione levels in the CNS of the ALS model wobbler mouse. We analyzed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Except for the upregulation of NLRP3, we could not detect any differences in pro-CASP 1 or c-CASP 1 levels in the cerebellum tissue among the p40 sample groups. Additionally, no significant difference was found when ROS levels in the cerebellum of the p40 wild-type and wobbler mice were compared [ 74 ]. The elevation of NLRP3 in the cerebellum could indicate the possible effect of NFκB on this gene; however, this increase alone does not guarantee inflammasome activation, which can also be inferred from unchanged levels of c-CASP 1 in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the upregulation of NLRP3, we could not detect any differences in pro-CASP 1 or c-CASP 1 levels in the cerebellum tissue among the p40 sample groups. Additionally, no significant difference was found when ROS levels in the cerebellum of the p40 wild-type and wobbler mice were compared [ 74 ]. The elevation of NLRP3 in the cerebellum could indicate the possible effect of NFκB on this gene; however, this increase alone does not guarantee inflammasome activation, which can also be inferred from unchanged levels of c-CASP 1 in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…282 Additionally, ultrastructural abnormalities were identified in the cerebellum of late-stage Wobbler mice. 283 The cerebellum in ALS also has exhibited oxidative stress abnormalities, 284 mitochondrial damage, 285 neurotransmitters and receptors changes, 277 and gene changes (Figure 3). 286,287 Structural and functional imaging studies have revealed structural and functional alterations in the cerebellum of ALS patients.…”
Section: Cerebellum and Alsmentioning
confidence: 99%
“…The complexity of the theme of this SI also brought to light the study conducted by Franziska T. Wunsch and colleagues, who studied defects in the glutathione system in an animal model of ALS [ 18 ]. The study, with an impressive bibliography, revealed that the reduced amount of glutathione obtained in the cervical spinal cord of wobbler mice is due to a decrease in glutathione synthesis due to a decrease in the expression of the speed-limiting enzyme glutamyl-cysteinyl-ligase.…”
mentioning
confidence: 99%
“…The study, with an impressive bibliography, revealed that the reduced amount of glutathione obtained in the cervical spinal cord of wobbler mice is due to a decrease in glutathione synthesis due to a decrease in the expression of the speed-limiting enzyme glutamyl-cysteinyl-ligase. For the first time, evidence has been provided for impaired glutathione metabolism in ALS in wobbler mice, not limited to motor areas of the CNS, with the need to study whether reduced glutathione is a causative factor or consequence of neurodegeneration into ALS, but with the opening of a possible targeted therapy for ALS by specifically improving glutathione synthesis [ 18 ].…”
mentioning
confidence: 99%